Tecnología de banda ancha: comunicación a través de la red de distribución eléctrica (2004)
The power-line communications (PLC) has been applied as a data transfer method in both public electricity distribution networks and indoor distribution networks. The profile of these applications has been different. The devices developed for domestic use are mainly designed for the purpose of controlling electric devices at home. For example, the current and most common functions are: control of lights, fire alarming system and heating controlling. The systems and devices used by distribution companies are mainly meant for automatic meter reading (AMR), tariff changing, energy consumption monitoring and load management applications. During the last years the conception of providing broadband Internet access through a low voltage distribution network has aroused a hot discussion. The characteristics of power-line channels and the applicability of different digital modulation techniques have been widely researched. Due to technical and regulatory problems, the idea of providing Internet services through the distribution network was at least partly buried. Despite of this drawback, the power-line channel is still an appropriate channel for to control devices and transfer data that do not require a wide bandwidth or critical data transfer. An example for this kind of application is data transfer related to the condition monitoring of industrial low voltage electric motors.